Nanomaterials and nanotechnology for the delivery of agrochemicals: strategies towards sustainable agriculture - An, Changcheng; Sun, Changjiao; Li, Ningjun; Huang, Bingna; Jiang, Jiajun; Shen, Yue; Wang, Chong; Zhao, Xiang; Cui, Bo; Wang, Chunxin; Li, Xingye; Zhan, Shenshan; et al. (Journal of nanobiotechnology, 2022)
Nanomaterials (NMs) have received considerable attention in the field of agrochemicals due to their special properties, such as small particle size, surface structure, solubility and chemical composition. The application of NMs and nanotechnology in agrochemicals dramatically overcomes the defects of conventional agrochemicals, including low bioavailability, easy photolysis, and organic solvent pollution, etc. In this review, we describe advances in the application of NMs in chemical pesticides and fertilizers, which are the two earliest and most researched areas of NMs in agrochemicals. Besides, this article concerns with the new applications of NMs in other agrochemicals, such as bio-pesticides, nucleic acid pesticides, plant growth regulators (PGRs), and pheromone. We also discuss challenges and the industrialization trend of NMs in the field of agrochemicals. Constructing nano-agrochemical delivery system via NMs and nanotechnology facilitates the improvement of the stability and dispersion of active ingredients, promotes the precise delivery of agrochemicals, reduces residual pollution and decreases labor cost in different application scenarios, which is potential to maintain the sustainability of agricultural systems and improve food security by increasing the efficacy of agricultural inputs. Graphical Abstract